Pelaksanaan Pasal 170 ayat 2 Kompilasi Hukum Islam terhadap Masa Berkabung Bagi Suami di Desa Ngimbang Kecamatan Palang Kabupaten Tuban - Efiana Nur Inayah; Mahir Amin (AL-HUKAMA, 2017)
This field research highlights "The Mourning Period for Husband in Ngimbang Village under the Islamic Law and Islamic Law Compilation (KHI) Perspective". The focus of the discussion are to find out the mourning period for husband who left by his wife died in Ngimbang, Palang, Tuban and how the Islamic law and Islamic Law Compilation (KHI) perspective. The results of the research known that the limit of declaring the mourning period for husband in Ngimbang Village divided into two, namely the mercy of the mourning period and the propriety of husband to marry again. The mercy of the mourning period is for 4 months and 10 days, while the propriety to marry again is 1000 days. As for the period of mourning, a husband should avoid the things that can cause slander, except for important purposes. These provisions are the product of socio-cultural that have long been guarded and do not violate the rules of Islam namely to avoid any slander. It has also been justified by Article 170 paragraph (2) Islamic Law Compilation, which mentions: "Husbands left by their wives should do mourning period according to appropriateness and decency." Therefore, husbands who have recently been abandoned by their wives should carry out a mourning period according to the propriety of their respective societies.